Mobile ad hoc robots and wireless robotic systems design and implelmentation - Aquino Santos, Raul, 1965-; Lengerke, Omar, 1975-; Block, Arthur Edwards, 1957- (Information Science Reference, 2013)
"This book introduces robotic theories, wireless technologies and routing applications involved in the development of mobile ad hoc robots"-- Provided by publisher.
Keywords: Mobile robots.; Ad hoc networks (Computer networks); elektronické knihy; electronic books